Pengujian Konstruk Literasi Keuangan Mahasiswa - Mukmin Mukmin; Ade Gunawan; Muhammad Arif; Jufrizen Jufrizen (JURNAL ILMIAH MANAJEMEN & BISNIS, 2021)
The purpose of this study was to produce a model for student financial literacy at the Faculty of Economics and Business, Private University in Medan. This study uses a quantitative approach with an ex post facto causal associative research design. This research was conducted at University of Muhammadiyah Sumatera Utara, Islamic University of North Sumatra, Pancabudi University, Dharmawangsa University, Al Azhar University, University of Muslim Nusantara, Al Washliyah University, Prima Indonesia University, HKBP Nomensen University, University of Prima Indonesia, and Sari Mutiara University. The study population was all students of the Faculty of Economics and Business, Private Universities in Medan City from semester IV to semester VIII. Data collection techniques using a list of questions (questionnaire), interviews and documentation studies. To test the dimensions of the financial literacy construct using structural equational modeling (SEM). The results showed that financial knowledge had a positive and significant effect on financial behavior, financial attitude had a positive and significant effect on financial behavior, and there was a significant reciprocal relationship between financial knowledge and financial attitude.